2020
DOI: 10.3390/app10155261
|View full text |Cite
|
Sign up to set email alerts
|

Combining Internal- and External-Training-Loads to Predict Non-Contact Injuries in Soccer

Abstract: The large amount of features recorded from GPS and inertial sensors (external load) and well-being questionnaires (internal load) can be used together in a multi-dimensional non-linear machine learning based model for a better prediction of non-contact injuries. In this study we put forward the main hypothesis that the use of such models would be able to inform better about injury risks by considering the evolution of both internal and external loads over two horizons (one week and one month). Predictive model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…It contained the data that were collected from 46 professional rugby league players throughout the 2015 NRL season, including some data collected by GPS (Global Positioning System). Similar approaches were presented in [ 13 , 14 ]. In these articles, the authors proposed their systems for predicting the possibility of the injury of the football players.…”
Section: Related Work and Existing Solutionsmentioning
confidence: 88%
“…It contained the data that were collected from 46 professional rugby league players throughout the 2015 NRL season, including some data collected by GPS (Global Positioning System). Similar approaches were presented in [ 13 , 14 ]. In these articles, the authors proposed their systems for predicting the possibility of the injury of the football players.…”
Section: Related Work and Existing Solutionsmentioning
confidence: 88%
“…Although other algorithms such as k-nearest neighbors (KNN) or extreme gradient boosting (XGBoost) showed a good predictive ability in previous studies (Rommers et al, 2020;Vallance, Sutton-Charani, Imoussaten, Montmain, & Perrey, 2020), they are often considered as blackbox models. The reason of this fact is linked to their difficulties of interpretation and their inability to provide information regarding the interaction between the different features (Cortez & Embrechts, 2013).…”
Section: Modelmentioning
confidence: 99%
“…The predicted maturity offset, defined as the years before or after PHV (Mirwald et al, 2002), is a useful non-invasive somatic indicator that predicts the time during which the athletes will experience their adolescent growth spurt (Malina, Bouchard, & Bar-Or, 2004). Particularly, the 6 months before and after PHV (maturity offset ranging from -0.5 to +0.5) have been identified as a critical period for the onset of injuries in young soccer players (Bult, Barendrecht, & Tak, 2018;van der Sluis et al, 2014). During this time, known also as the period of 'adolescent awkwardness' (Philippaerts et al, 2006), young athletes experience a decline in performance and motor control.…”
Section: Modelmentioning
confidence: 99%
“…In soccer, running performance (RP) has been extensively studied over the last two decades [1,2]. Detailed knowledge about this performance in match play is essential for the design and implementation of specific fitness training [3][4][5][6]. Previous studies have demonstrated that players regularly transit between brief bouts of high-intensity running and longer periods of low-intensity running [1,7].…”
Section: Introductionmentioning
confidence: 99%